2004
DOI: 10.1126/science.1096437
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in a Human ROBO Gene Disrupt Hindbrain Axon Pathway Crossing and Morphogenesis

Abstract: The mechanisms controlling axon guidance are of fundamental importance in understanding brain development. Growing corticospinal and somatosensory axons cross the midline in the medulla to reach their targets and thus form the basis of contralateral motor control and sensory input. The motor and sensory projections appeared uncrossed in patients with horizontal gaze palsy with progressive scoliosis (HGPPS). In patients affected with HGPPS, we identified mutations in the ROBO3 gene, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
310
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 354 publications
(320 citation statements)
references
References 24 publications
8
310
1
1
Order By: Relevance
“…Marillat et al (2004) have demonstrated a role for Rig1/Robo3 in controlling midline crossing of hindbrain precerebellar neurons and axons. Human patients with horizontal gaze palsy with progressive scoliosis (HGPPS) were reported to have mutations in Rig1/ Robo3, and functional studies have shown defects in commissural hindbrain projections and pontine nuclei (Jen et al, 2004). Gilthorpe et al (2002) have shown that early and late stage chick cerebellar rhombic lip fragments are repelled by Slit2.…”
Section: Discussionmentioning
confidence: 99%
“…Marillat et al (2004) have demonstrated a role for Rig1/Robo3 in controlling midline crossing of hindbrain precerebellar neurons and axons. Human patients with horizontal gaze palsy with progressive scoliosis (HGPPS) were reported to have mutations in Rig1/ Robo3, and functional studies have shown defects in commissural hindbrain projections and pontine nuclei (Jen et al, 2004). Gilthorpe et al (2002) have shown that early and late stage chick cerebellar rhombic lip fragments are repelled by Slit2.…”
Section: Discussionmentioning
confidence: 99%
“…These isoforms of Robo3 have different affinities to Slit2 (Camurri et al, 2005). In humans, a point mutation in the Robo3 isoform A signal peptide results in horizontal gaze palsy with progressive scoliosis (HGPPS), even though the Robo3 isoform B remains intact (Jen et al, 2004). This raises an interesting point for future determination of Slit binding characteristics of Robo1 and Dutt1.…”
mentioning
confidence: 99%
“…The first roundabout gene, Robo, was identified in Drosophila in a screen for genes regulating midline crossing in the CNS (Seeger et al, 1993). Three Robo genes have been found in Drosophila (Kidd et al, 1998;Rajagopalan et al, 2000a;Simpson et al, 2000b) and mammals Li et al, 1999;Yuan et al, 1999;Jen et al, 2004), and one in Caenorhabditis elegans (Zallen et al, 1998). Mammalian Slits can bind to all Robo receptors with comparable affinity Li et al, 1999;Sabatier et al, 2004).…”
Section: Introductionmentioning
confidence: 99%